Market Segmentation Strategies for the Dissemination of New Agricultural Production Technologies: Experimental Delivery of Laser Land Leveling to Farmers in Uttar Pradesh, India - International Food Policy Research Institute; University of California, Davis; University of Georgia (International Food Policy Research Institute, 2017)
This dataset contains observations from 478 households interviewed in 2011 and 2012 as part of a study titled “Market segmentation strategies for the dissemination of new agricultural production technologies in India.” The data were collected as part of a demand elicitation exercise and randomized control trial of custom-hired laser land leveling services provided to study participants. The study was conducted in the Maharajganj, Gorakhpur, and Deoria districts of eastern Uttar Pradesh, India under the auspices of the Cereal Systems Initiative for South Asia (CSISA). These three districts represent the regional spectrum of productivity in rice–wheat cropping systems. From each district, eight villages were randomly selected from a population of villages that met specific criteria set forth in the publications noted above. In addition to household data on the study participants, the dataset contains information on 926 plots cultivated by the study participants. Aside from household survey data, this study also contains data from village, social network, and monitoring surveys.